Harry Potter and the goblet of fire - Rowling, J.K.; Grandpre, Mary (New York Arthur A. Levine, 2000)
Harry Potter, a fourth-year student at Hogwarts School of Witchcraft and Wizardry, longs to escape his hateful relatives, the Dursleys, and live as a normal fourteen-year-old wizard, but what Harry does not yet realize is that he is not a normal wizard, and in his case, different can be deadly.
Sequel to: Harry Potter and the prisoner of Azkaban.
Keywords: Wizards; Magic; Schools; England; Fantasy fiction